Apoyo social y calidad de vida en cuidadores de niños con enfermedades crónicas - Quintero Bolaños, Claudia Lorena (Universidad Antonio Nariño, 2023)
To establish the level of association between social support and health-related quality of life in caregivers of children with chronic pathologies